An Assessment of the Impact of Technological Innovations on Electoral Credibility in Nigeria, 2015 to 2023 - Oluwaseun Clement Ajayi; Abraham Musa Peter; Margaret Apine (Darul Yasin Al Sys, 2026)
Although the Nigerian government has introduced a range of technological innovations between 2015 and 2023, including the Smart Card Reader, Bi-modal Accreditation Voter System (BVAS), the INEC Result Viewing Portal (IReV), and Result Transmission Platforms to curb electoral malpractice, concerns about electoral credibility persist. This study aims to assess the extent to which these technologies enhanced electoral credibility in Nigeria’s 2015, 2019, and 2023 general elections. Drawing on institutional theory as the analytical lens, the study employs a documentary secondary analysis of journal articles, election reports, academic literature, and international election observer reports to evaluate the performance and limitations of electoral technologies. The findings reveal that the introduction of these technologies has reduced manipulations and fraud, including multiple voting, inflated results, and related irregularities, thereby contributing to improved transparency and electoral integrity. However, the study also identifies persistent constraints, such as infrastructure deficits, political interference, technical failures, weak institutional frameworks, insecurity, poor logistics, and pervasive vote buying, which collectively undermine the effectiveness and credibility-enhancing potential of these innovations. Despite these challenges, the 2023 general elections recorded notable progress in the deployment and acceptance of electoral technologies. The study concludes that although technology is necessary for improving the electoral process, it is insufficient to guarantee electoral credibility without robust political will, comprehensive legal and institutional reforms, and active public engagement. The study contributes to the literature on electoral governance and technology by highlighting the conditions under which technological innovations can genuinely enhance electoral credibility and by underscoring the need for civic education, transparent and efficient technological deployment, and stronger institutions to support democratic consolidation.